EFFECTS OF ZEOLITE AND LIQUID WASTE OF MSG (MONOSODIUM GLUTAMATE) ON PRODUCT OF NILAM PLANT (Pagostemon Cablin BENTH) IN ULTISOLS - Any Kusumastuti; Jonathan Parapasan; Dewi Riniarti (Institut Teknologi Bandung, 2007)
Ultisols is soil which predominate area in Lampung Province. This soil is rather acid until acid reaction, low in cation exchange capacity (CEC) and organic materials content so that cause inefficient of fertilization. Zeolite is a available and potential mining products and it is abundant available in Lampung Province. It can also to improve CEC of soil so that the absorption of soil to fertilizer can be increased. Besides, it has a high negative charges, so that it can also absorbed of nutrients and discharged it slowly. A liquid waste of MSG is an agroindustrial waste which enough potential. The waste contains the high enough organic materials and compound, especially nitrogen. Low of organic materials at Ultisols, caused needed an input to this management, for example combination usage of zeolite and liquid waste MSG. Nilam is plantation crop which have a good enough prospect, and have potency as state resource of stock-exchange and also can open the new employment. This research arranged in garden of Lampung State Polytechnic, Hajimena district, with Ultisols, it